A method for detecting weak signals using chaotic systems based on multiple correlation and phase-locked loop. (September 2020) - He, Qiurui; Li, Deguang; Jin, Yanling; Zhang, Yang; Zhang, Lanjie
Abstract: In order to improve the detection ability of chaotic system to detect weak periodic signal frequency, phase and amplitude, a chaotic system based on multiple correlation and phase-locked loop is established. Firstly, the signal to be measured is input into the detection frequency of chaotic system. Also, the reference signal of multiple correlation technology is constructed, and the signal to be tested is processed by multiple cross-correlation. Then, the signal processed by multiple correlation is input into the phase-locked loop to obtain the phase of the signal to be measured. Finally, the signal to be measured is input into the chaotic system again, and the amplitude of the signal to be measured is detected according to the change of the chaotic oscillator in critical periodic state and large-scale periodic state. The experimental results show that the detection system can detect the frequency, phase and amplitude of weak periodic signal, which is easy to operate and has high detection ability.